Cerebral Edema in Patients with severe Hemispheric Syndrome: Incidence, Risk Factors, and Outcomes—Data from SITS-ISTR - Irene Escudero-Martínez; Magnus Thorén; Peter Ringleb; Ana Paiva Nunes; Manuel Cappellari; Viiu-Marika Rand; Piotr Sobolewski; Jose Egido; Danilo Toni; Shih-Yin Chen; Nicole Tsao; Niaz Ahmed (Journal of Stroke, 2023)
Background and Purpose Cerebral edema (CED) in ischemic stroke can worsen prognosis and about 70% of patients who develop severe CED die if treated conservatively. We aimed to describe incidence, risk factors and outcomes of CED in patients with extensive ischemia. Methods Oservational study based on Safe Implementation of Treatments in Stroke-International Stroke Treatment Registry (2003–2019). Severe hemispheric syndrome (SHS) at baseline and persistent SHS (pSHS) at 24 hours were defined as National Institutes of Health Stroke Score (NIHSS) >15. Outcomes were moderate/severe CED detected by neuroimaging, functional independence (modified Rankin Scale 0–2) and death at 90 days. Results Patients (n=8,560) presented with SHS and developed pSHS at 24 hours; 82.2% received intravenous thrombolysis (IVT), 10.5% IVT+thrombectomy, and 7.3% thrombectomy alone. Median age was 77 and NIHSS 21. Of 7,949 patients with CED data, 3,780 (47.6%) had any CED and 2,297 (28.9%) moderate/severe CED. In the multivariable analysis, age <50 years (relative risk [RR], 1.56), signs of acute infarct (RR, 1.29), hyperdense artery sign (RR, 1.39), blood glucose >128.5 mg/dL (RR, 1.21), and decreased level of consciousness (RR, 1.14) were associated with moderate/severe CED (for all P<0.05). Patients with moderate/severe CED had lower odds to achieve functional Independence (adjusted odds ratio [aOR], 0.35; 95% confidence interval [CI], 0.23 to 0.55) and higher odds of death at 90 days (aOR, 2.54; 95% CI, 2.14 to 3.02). Conclusions In patients with extensive ischemia, the most important predictors for moderate/ severe CED were age <50, high blood glucose, signs of acute infarct, hyperdense artery on baseline scans, and decreased level of consciousness. CED was associated with worse functional outcome and a higher risk of death at 3 months.